From Representation to Responsibility: Paul Bowles’s Moroccan Translations and the Ethics of Listening - Youssefi, Imad (International Journal of Linguistics and Translation Studies, 2026)
This article re-examines Paul Bowles’s translations of Moroccan oral narratives through an ethical and hermeneutic lens. Moving beyond charges of Orientalism and exploitation, it argues that Bowles’s work constitutes a form of linguistic hospitality—an act of listening that welcomes the foreign without erasing its difference. Drawing on the theoretical frameworks of Antoine Berman, Lawrence Venuti, Paul Ricoeur, and Gayatri Spivak, the paper situates Bowles’s collaborations with Mohamed Choukri, Mohammed Mrabet, and Larbi Layachi as negotiations between fidelity, authority, and affection. His insistence on rereading translations with storytellers, his preservation of Moroccan idioms and oral rhythms, and his refusal to domesticate difference reveal a translator attentive to the rhetoricity of the original rather than to fluency alone. The conflict with Choukri, as documented in Paul Bowles wa ʿUzlat Ṭanja Ṭanja and Al-Ḥiwār al-Ākhir, is reinterpreted as a moral dialogue revealing both the vulnerability and endurance of cross-cultural trust. Ultimately, Bowles’s translations emerge as ethical experiments in coexistence—attempts to sustain conversation across inequality and language itself. Translation, in this view, is not the resolution of difference but its preservation through care, humility, and the courage to keep listening.